How Romantic Relationships Shape Self-Worth: A Qualitative Exploration of Relationship Contingent Self-Esteem in Early Adulthood - Syafiyah, Aufizzahra As; Hartati, Niken; Primanita, Rida Yanna (Utan Kayu Publishing, 2025)
Romantic relationships in early adulthood have been shown to have a significant impact on an individual's sense of self-worth, particularly when self-esteem becomes dependent on relational dynamics. This study explores the manifestation and impact of Relationship Contingent Self-Esteem (RCSE) on psychological well-being among young adults in Padang, Indonesia. A qualitative survey approach was utilized to collect data from 200 participants (75 males and 125 females) through open-ended questionnaires designed to capture personal experiences and perceptions related to self-worth in romantic contexts. Thematic analysis was conducted using MAXQDA software in three stages: open coding to identify key concepts, axial coding to uncover patterns, and selective coding to synthesize overarching themes. The findings of the present study indicate that external validation from romantic partners plays a pivotal role in shaping self-evaluation and emotional states. Dependence on partner approval has been demonstrated to correspond with fluctuations in self-esteem, which in turn has been demonstrated to impact overall psychological well-being. The findings underscore the importance of addressing emotional vulnerabilities in romantic relationships. The necessity for targeted interventions, such as psychoeducational programs and emotional regulation training, is also suggested. The purpose of these interventions is to foster emotional resilience and promote healthy relational development during early adulthood.